Land loss in the Mississippi River Delta: Role of subsidence, global sea-level rise, and coupled atmospheric and oceanographic processes - Blum, Mike; Rahn, David; Frederick, Bruce; Polanco, Sara (Global and planetary change, 2023)
The Mississippi River Delta in coastal Louisiana has suffered large-scale land loss during the historic period and is representative of a global phenomenon where low-elevation deltaic coasts are increasingly at risk because of disrupted sediment supply and accelerated global sea-level rise. Land loss is a natural part of deltaic evolution over time, and most of the land loss in the Mississippi River Delta occurred after individual delta-plain headlands were abandoned as active constructional landscapes, but before 1932 when collection of air photos would make repeat land loss measurements possible. A coastwide land loss of ∼5000 km2 is now well documented for the period 1932 to 2016, which corresponds to a mean rate of ∼57 km2 yr−1. We use a LiDAR digital topobathymetric model to hindcast land-area changes through time for 1950–2010 by incrementally restoring elevation lost due to subsidence, global sea-level rise, and annual anomalies in mean sea level. Our results support the view that the magnitude and spatial distribution of 20th century land loss can be explained by an unfortunate convergence of ongoing subsidence, greatly reduced sediment dispersal due to levee construction, and acceleration of global sea-level rise. Other factors have contributed to land loss on local scales, but the magnitude of land loss that has occurred would have occurred anyway due to subsidence, lack of sediment input, and accelerated sea-level rise. Multidecadal accelerations and decelerations in land loss from 1950 to 2010 have been observed, and attributed to accelerations and decelerations in subsidence due to subsurface fluid withdrawals. However, non-linear land loss represents measurements that were made when water levels varied due to annual to multidecadal anomalies in mean sea level. Anomalies in mean sea level are driven by flux of water into and out of the Gulf of Mexico from the Atlantic, as well as the Atlantic Multidecadal Oscillation (AMO), which produces precipitation anomalies in the Gulf of Mexico drainage area, anomalies in Mississippi River discharge to the Gulf of Mexico, and changes in wind directions that serve to trap water along the coast and elevate coastal sea level, or advect water away from the coast to lower coastal sea level. Sea-level anomalies of the scale described here amplify or suppress the secular trend of global sea-level rise and its impacts on low-elevation delta plains as they respond to ongoing subsidence and anthropogenic disruption of sediment dispersal. •The late Holocene Mississippi River Delta experienced widespread land loss prior to and in the 20th century, land loss that continues to this day•More than half of the total land loss occurred after individual delta plains were abandoned as constructional landscapes but prior to the 1930s•Century-scale land loss rates reflect ongoing subsidence, reduced sediment input from levee construction, and accelerated global sea-level rise•Over annual to multidecadal timescales, land loss rates change due to naturally occurring sea level anomalies that amplify and suppress loss rates•Land loss reflects interactions between subsidence, human actions, accelerated sea-level rise, and atmospheric and oceanographic processes